2023
DOI: 10.1111/agec.12767
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐edited or genetically modified food? The impacts of risk and ambiguity on Chinese consumers' willingness to pay

Abstract: This study investigates consumer preferences for newly introduced gene‐edited (GE) food. We focus on how risk and ambiguity aversion affect consumers’ willingness to pay (WTP) to avoid genetically modified (GM) food or GE food and whether the impacts of risk and ambiguity aversion differ between GM and GE food. We collected the data in 2020 through a nationwide online survey in China. The multiple price list method is used to estimate the premiums that consumers are willing to pay for conventional rice to avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Thus, a direct comparison of this result with previous studies may not be possible. One exception is Ding et al (2023), who used the same scale and found a negative link between ambiguity aversion and GM/GE acceptance. The divergence between our results and theirs might be a consequence of differences in the application of the scale-we used the exact scale developed by McLain (2009) while they adapted the scale to measure ambiguity aversion rather than tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, a direct comparison of this result with previous studies may not be possible. One exception is Ding et al (2023), who used the same scale and found a negative link between ambiguity aversion and GM/GE acceptance. The divergence between our results and theirs might be a consequence of differences in the application of the scale-we used the exact scale developed by McLain (2009) while they adapted the scale to measure ambiguity aversion rather than tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, risk‐loving behavior is positively correlated with WTP for GE. Since studies have established that food biotechnology is considered risky food by consumers (Ding et al, 2023; Lusk & Coble, 2005), it is expected that risk loving consumers will be more willing to accept these foods. These results confirm that risk perceptions and risk preference are both critical in explaining consumers' attitudes toward food biotechnology and should be considered by stakeholders in the food biotechnology industry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations